Diabetes, gender, and left ventricular structure in African-Americans: the atherosclerosis risk in communities study - Liebson Philip R; Benjamin Emelia J; Arnett Donna K; Duncan Bruce B; Foppa Murilo; Manolio Teri A; Skelton Thomas N (Cardiovascular Ultrasound, 2006)
Abstract Background Cardiovascular risk associated with diabetes may be partially attributed to left ventricular structural abnormalities. However, the relations between left ventricular structure and diabetes have not been extensively studied in African-Americans. Methods We studied 514 male and 965 female African-Americans 51 to 70 years old, in whom echocardiographic left ventricular mass measurements were collected for the ARIC Study. In these, we investigated the independent association of diabetes with left ventricular structural abnormalities. Results Diabetes, hypertension and obesity prevalences were 22%, 57% and 45%, respectively. Unindexed left ventricular mass was higher with diabetes in both men (238.3 ± 79.4 g vs. 213.7 ± 58.6 g; p < 0.001) and women (206.4 ± 61.5 g vs. 176.9 ± 50.1 g; p < 0.001), respectively. Prevalence of height-indexed left ventricular hypertrophy was higher in women while increased relative wall thickness was similar in men and women. Those with diabetes had higher prevalences of height-indexed left ventricular hypertrophy (52% vs. 32%; p < 0.001), and of increased relative wall thickness (73% vs. 64%; p = 0.002). Gender-adjusted associations of diabetes with left ventricular hypertrophy (OR = 2.29 95%CI:1.79–2.94) were attenuated after multiple adjustments in logistic regression (OR = 1.50 95%CI:1.12–2.00). Diabetes was associated with higher left ventricle diameter (OR = 2.13 95%CI:1.28–3.53) only in men and with higher wall thickness (OR = 1.89 95%CI:1.34–2.66) only in women. Attenuations in diabetes associations were frequently seen after adjustment for obesity indices. Conclusion In African-Americans, diabetes is associated with left ventricular hypertrophy and, with different patterns of left ventricular structural abnormalities between genders. Attenuation seen in adjusted associations suggests that the higher frequency of structural abnormalities seen in diabetes may be due to factors other than hyperglycemia.